Differential effects of the rhizobacterium Pseudomonas simiae on above‐ and belowground chewing insect herbivores. (26th November 2020) - Friman, Julia; Pineda, Ana; Gershenzon, Jonathan; Dicke, Marcel; van Loon, Joop J. A.
Abstract: Plant growth‐promoting rhizobacteria (PGPR) can enhance plant growth and defence. Via plant‐mediated effects, PGPR have been reported to impact the performance of generalist leaf‐chewing insects either negatively or positively. However, only a few insect species, mainly feeding on aboveground tissues, have thus far been investigated. Here, we investigated how addition of rhizobacteria to the soil in which cabbage plants are growing affects the performance of three chewing insect herbivores, two leaf chewers and one root feeder. In a greenhouse experiment, we grew white cabbage ( Brassica oleracea ) plants in soil supplemented with and without the rhizobacterium Pseudomonas simiae WCS417r. We investigated the consequences for three important insect pests of Brassica species, larvae of the cabbage moth Mamestra brassicae, the diamondback moth Plutella xylostella, or the cabbage root fly Delia radicum after 5 weeks of plant growth. We recorded aboveground plant biomass, insect biomass, plant defence marker gene expression levels and plant defence‐related hormone concentrations. Rhizobacterial inoculation increased aboveground plant biomass in non‐infested plants but not in infested plants. Rhizobacterial inoculation affected insect performance differently: on PGPR‐inoculated plants biomass of Plutella xylostella was lower, while biomass of Delia radicum was higher than on control plants. However, no effect was found on Mamestra brassicae biomass. Rhizobacterial inoculation increased the expression of the defence marker gene LOX2 in P. xylostella‐ infested plants and MYC2 in M. brassicae ‐infested plants. Transcription levels of the plant defence marker gene PAL1 showed upregulation between inoculated and non‐inoculated insect‐free plants. Levels of the phytohormones jasmonic acid, salicylic acid and abscisic acid were similar in inoculated and non‐inoculated plants. We conclude that rhizobacterial inoculation has potential to be applied in the protection of cabbage crops against the diamondback moth whereas this does not apply to reducing damage caused by the cabbage moth or cabbage root fly.